Pengaruh Kualitas Produk, Citra Merek, Label Halal, dan Harga terhadap Kepuasan Konsumen Generasi Z pada Produk Skincare Wardah di Jepara - Nila Fauziyah; Mahmudatus Sa’diyah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the influence of product quality, brand image, halal certification, and price on Generation Z consumer satisfaction with Wardah skincare products in Jepara Regency. Generation Z is a consumer segment that is digitally savvy, critical, and considers both functional aspects and values when choosing skincare products. This study employs a quantitative approach using a survey method. Data collection was conducted via a questionnaire administered to 150 Generation Z respondents who use Wardah skincare products in Jepara, utilizing purposive sampling. Data analysis employed the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method using the SmartPLS software. The results indicate that halal labeling, price, and brand image have a positive and significant influence on the satisfaction of Generation Z consumers who use Wardah skincare products in Jepara. Conversely, product quality does not significantly influence consumer satisfaction, as Generation Z consumers tend to perceive Wardah skincare quality as already meeting standard levels, thus no longer serving as a primary differentiating factor in shaping satisfaction. This study is expected to provide theoretical contributions to the development of research on Generation Z consumer behavior, as well as practical insights for Wardah in formulating marketing strategies and developing skincare products aligned with local consumer characteristics.